A cross sectional study of cutaneous manifestations in 300 patients of diabetes mellitus - Khuraiya, Sandeep; Lal, Nancy; ., Naseerudin; Jain, Vinod; Kachhawa, Dilip (International Journal of Advances in Medicine, 2019)
Background: Diabetes Mellitus (DM) is a worldwide problem and one of the most common endocrine disorder. The skin is affected by both the acute metabolic derangements and the chronic degenerative complications of diabetes. Methods: The present study was a one-year cross sectional study from January 2014 to December 2014. All confirmed cases of DM with cutaneous manifestations irrespective of age, sex, duration of illness and associated diseases, willing to participate in the study were included in the study. Routine haematological and urine investigations, FBS, RBS and HbA1c levels were carried out in all patients. Results: A total of 300 patients of diabetes mellitus with cutaneous manifestations were studied. Majority belonged to the 4th decade (33%) and 3rd decade (27.7%) respectively. Males constituted 65% of the cases and male to female ratio was 1.85:1. Type 2 DM was most commonly observed (96%). Among the 300 diabetic patients, 73 patients (24.3%) had good control of DM with HbA1c levels in the range of 6.5-7% while 132 patients (44%) had a poor control of DM with HbA1c levels >8%. Hypertension was the most commonly associated systemic illness (37.6%). Cutaneous infections (63%) were the most commonly observed manifestation of which fungal infections (35.3%) were most frequently observed. Some of the other dermatoses observed were generalized pruritus (15.3%), acrochordons (11%), acanthosis nigricans (6%), diabetic dermopathy (5.33%), diabetic foot (3%), peripheral vascular disease (2.66%), vitiligo (2.66%), xanthelasma palpebrarum (2.33%), diabetic bullae (1%). Cutaneous infections, dermatoses associated with microangiopathy were more common in the uncontrolled diabetic patients which was statistically significant. Conclusions: Infections were the most common cutaneous manifestations in diabetics followed by dermatoses most commonly associated with diabetes. Proper skin care and long-term control of blood glucose levels may reduce the risk of some of the skin diseases.